Autoimmune hepatitis vs. pregnancy - Adamczyk-Gruszka, Olga; Lewandowska-Andruszuk, Izabela; Gruszka, Jakub; Komar-Gruszka, Karolina (Journal of Education, Health and Sport, 2017)
Introduction Autoimmune hepatitis (AIH) is a disease of unknown etiology. In pregnancy, it may have mild clinical course as well as can lead to liver failure, or exacerbation of clinical symptoms. In pregnant women the severity of symptoms is often observed between the second and third trimester, and in the puerperium. The disease is marked by enhanced activity of Th lymphocytes, which hepatocytes recognize as foreign antigens. This results in interleukin production activating B lymphocytes, and the production of specific antibodies attacking and destroying the hepatocytes. Case report A 35-year old patient, CII PII, 7 Hbd, with autoimmune hepatitis reported for a check-up. Her first pregnancy was 18 years ago, without history of underlying disease, carried to term without complications. The woman gave birth to a baby-son weighing 3,280g, 10 points Apgar. The delivery was spontaneous and uneventful. The patient got pregnant after an 18-year break. When she twice-tested positively for pregnancy, the treatment with azathioprine was switched to prednisolone. Over the pregnancy the patient was hospitalized 4 times, in 25, 29, 35, and 37 week of gestation due to a threat of preterm delivery, and pregnancy-related cholestasis associated with AIH. In 37 week of gestation, delivery was induced, and she gave birth to a healthy male, weighing 2,650 g, body height of 49 cm, 10 points Apgar scale. The liver function improved and stabilized after the delivery. Treatment with prednisolone has been continued, and the patient’s condition is still controlled. Pregnant patients with autoimmune hepatitis often experience exacerbation of the disease, especially in the third trimester, and in the postpartum period. This case shows that with proper care it is possible to continue and terminate pregnancy safely for the mother and her newly born baby.